2011
DOI: 10.1002/ep.10593
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of chloroform adsorption onto fixed‐bed columns of highly siliceous granular zeolites

Abstract: Adsorption of chloroform to granular ZSM‐5 zeolite in fixed‐bed columns was measured and the breakthrough curves predicted with a film‐pore and surface diffusion (FPSD) model. Parameters for the FPSD model were estimated from published correlations and from data taken from batch adsorption rate studies. It was found that the adsorption rate was enhanced with decrease in particle size, however, the total adsorption capacity using granular ZSM‐5 with different particle sizes remained constant. The FPSD model acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Currently, a variety of mathematical models have been used to describe and predict the breakthrough curves of a column adsorption system in liquid or gaseous phase (Abu-Lail et al, 2012;Cheknane et al, 2012;Meng et al, 2012;Nwabanne and Igbokwe, 2012;Yi et al, 2012;Zhao et al, 2012), but there is still lack of a comprehensive review of these models. The main objective of the present review is to introduce the modeling of dynamic adsorption in liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a variety of mathematical models have been used to describe and predict the breakthrough curves of a column adsorption system in liquid or gaseous phase (Abu-Lail et al, 2012;Cheknane et al, 2012;Meng et al, 2012;Nwabanne and Igbokwe, 2012;Yi et al, 2012;Zhao et al, 2012), but there is still lack of a comprehensive review of these models. The main objective of the present review is to introduce the modeling of dynamic adsorption in liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the wealth of literature on equilibrium and kinetic parameters for mass transfer, relatively few papers have considered sensitivity to heat transfer parameters 9,21,23,31,[40][41][42][43] . This is partially due to the simplifying assumption made in many studies [2][3][4][5][6][7][8][10][11][12][13][14][15][16][17][24][25][26]30,32,34 to neglect heat transfer and treat the entire bed as isothermal. This assumption is made despite the fact that system-level models of cyclic pressure and temperature-swing-adsorption processes are known to be highly sensitive to temperature variations 20 .…”
Section: Axial Dispersion Is a Complex Function Of Flow Conditions Anmentioning
confidence: 99%
“…Conclusions in the literature regarding sensitivity to axial dispersion are less consistent; while many researchers concluded that adsorption models are insensitive to axial dispersion 3,4,10,12,14,21,26,30 , others found the opposite to be true 16,24,25,33 . Yet others are equivocal in their conclusions.…”
Section: Introductionmentioning
confidence: 97%